1990
DOI: 10.1136/oem.47.12.810
|View full text |Cite
|
Sign up to set email alerts
|

An update of cancer mortality among chrysotile asbestos miners in Balangero, northern Italy.

Abstract: The mortality experience of a cohort of chrysotile miners employed since 1946 in Balangero, northern Italy was updated to the end of 1987 giving a total of 427 deaths out of 27 010 man-years at risk. A substantial excess mortality for all causes (standardised mortality ratio (SMR) = 149) was found, mainly because of high rates for some alcohol related deaths (hepatic cirrhosis, accidents). For mortality from cancer, however, the number of observed deaths (82) was close to that expected (76-2). The SMR was rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 16 publications
2
66
0
Order By: Relevance
“…In this study, oro-pharyngeal and laryngeal cancers presented similar results: seven male and no female deaths, and 2.3-fold elevated SMR, comparable to other Italian asbestos-exposed cohorts (Piolatto et al, 1990;Puntoni et al, 2001). Since these findings may simply reflect bias or confounding (Griffiths and Malony, 2003), we computed expected deaths and SMR for male laryngeal cancer also applying Piedmont regional mortality rates, which were available from 1970 but the SMR decreased only slightly, to 213.5.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, oro-pharyngeal and laryngeal cancers presented similar results: seven male and no female deaths, and 2.3-fold elevated SMR, comparable to other Italian asbestos-exposed cohorts (Piolatto et al, 1990;Puntoni et al, 2001). Since these findings may simply reflect bias or confounding (Griffiths and Malony, 2003), we computed expected deaths and SMR for male laryngeal cancer also applying Piedmont regional mortality rates, which were available from 1970 but the SMR decreased only slightly, to 213.5.…”
Section: Discussionsupporting
confidence: 79%
“…Cohort studies found increased incidence and mortality from mesothelioma among (chiefly male) asbestos workers employed in mining (Piolatto et al, 1990;McDonald et al, 1993), but mainly textile and manufacture (Newhouse and Berry, 1979;Berry et al, 2000;Yano et al, 2001), insulation (Selikoff et al, 1979) and asbestos-cement factories (Tulchinsky et al, 1999;Ulvestad et al, 2002). Mesothelioma risk varied widely among different studies, according to types of asbestos involved (chrysotile, amosite or crocidolite) (Hodgson and Darnton, 2000) and levels of exposure (Doll and Peto, 1985).…”
mentioning
confidence: 99%
“…With α allowed to vary (α = 0.937) the estimate is K L = 0.00051 (f-yr/ml) −1 with 90% CI: (0, 0.0057). Two mesotheliomas were observed by Piolatto et al (1990), compared to one found by Rubino et al (1979). However, data were not presented in a form that allowed K M to be estimated.…”
Section: Italian Mine and Millmentioning
confidence: 99%
“…Lung cancer was neither significantly in excess nor was it significantly related to cumulative asbestos exposure. Piolatto et al (1990, Table 1) presented observed and expected lung cancers (based on ageand calendar-year-specific rates for Italian men) categorized by cumulative exposure in f-yr/ml. The lung cancer model [Eq.…”
Section: Italian Mine and Millmentioning
confidence: 99%
See 1 more Smart Citation